Time to Listen: Most Regular Patrons of Music Venues Prefer Lower Volumes - Beach, Elizabeth Francis; Gilliver, Megan (Frontiers in Psychology, 2019)
High sound levels are a feature of nightclubs and live music venues, and therefore pose a risk to patrons’ hearing. As a result, these venues are often a focus area for hearing health promotion, and particular emphasis is placed on motivating patrons to take steps to reduce their noise exposure. In the current study, we approached this issue from a different angle. We asked whether sound levels in music venues accurately reflect the preferences of regular patrons, and examined their attitudes and preferences towards sound levels and protective listening behaviours. The study examined results from 993 regular patrons of nightclubs and live music venues, collected as part of an Australian online hearing health survey. Participants were asked about their participation at the two target venues, experiences of hearing difficulties, and risk perceptions. They were also asked about their preferences in relation to typical venue sound levels and beliefs about other attendees’ preferences. Results showed that while participants generally rated their hearing as good, the majority had experienced hearing difficulties following sound exposure at music venues. The majority of regular patrons were dissatisfied with current sound levels, with around three-quarters of participants reporting preferences below the levels typically experienced at music venues. Participants were generally aware of the risk posed by high sound levels and those who regarded themselves to be at greater risk from attending music venues were more likely to prefer lower sound levels. These findings have important consequences for the development of hearing health initiatives within entertainment venues. Rather than motivating patrons to change their behavior, encouraging venues to meet their patrons’ needs and preferences may be a more successful strategy. Venue operators may find that this approach has a positive impact not only on the hearing health of patrons, but also on the economic health of their venue. Ultimately, reducing the hearing risk in music venues may best be achieved not by telling people what to do, but by listening to what they actually want.